The best damn Windows Server 2008 book period - Piltzecker, Tony, 1975- (Syngress ; Elsevier Science [distributor], 2008)
The Second Edition of the Best Damn Windows Server Book Period is completely revised and updated to Windows Server 2008. This book will show you how to increase the reliability and flexibility of your server infrastructure with built-in Web and virtualization technologies; have more control over your servers and web sites using new tools like IIS7, Windows Server Manager, and Windows PowerShell; and secure your network with Network Access Protection and the Read-Only Domain Controller. New to this Edition: * Web server management with Internet Information Services 7.0 * Virtualize multiple operating systems on a single server * Hardening Security, including Network Access Protection, Federated Rights Management, and Read-Only Domain Controller.